2004
DOI: 10.1103/physrevd.70.073002
|View full text |Cite
|
Sign up to set email alerts
|

Large logarithms in the beam normal spin asymmetry of elastic electron-proton scattering

Abstract: We study a parity-conserving single-spin beam asymmetry of elastic electron-proton scattering induced by an absorptive part of the two-photon exchange amplitude. It is demonstrated that excitation of inelastic hadronic intermediate states by the consecutive exchange of two photons leads to logarithmic and double-logarithmic enhancement due to contributions of hard collinear quasi-real photons. The asymmetry at small electron scattering angles is expressed in terms of the total photoproduction cross section on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 29 publications
7
70
6
Order By: Relevance
“…The predictions of Eqs. (47,49) are confronted with the experimental data of Ref. [47] at high energies and for Q 2 that ranged from zero to several GeV 2 in Fig.…”
Section: Uncertainty In Isospin Rotating the Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The predictions of Eqs. (47,49) are confronted with the experimental data of Ref. [47] at high energies and for Q 2 that ranged from zero to several GeV 2 in Fig.…”
Section: Uncertainty In Isospin Rotating the Backgroundmentioning
confidence: 99%
“…However, real experiments are carried out at finite momentum transfer t, in particular |t| = 0.03 GeV 2 for the kinematics of the QWEAK experiment. To extrapolate the forward sum rule to non-zero momentum transfer, we employ the phenomenological model that was successfully used for the beam normal spin (Mott) asymmetry in elastic ep-scattering [49][50][51]. This model is inspired by i) experimental data on the Compton differential cross section at small t and high energy, and ii) the assumption of the predominantly imaginary phase of the Compton amplitude at high energies (as for the pomeron).…”
Section: Additional T-dependence Of Dispersion Correctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent calculations have shown that in the forward kinematics, a logarithmic enhancement takes place [13], but the contribution of the ln 2 (−t/m 2 ) term comes with photon helicity flip amplitude of RCS and its contribution is negligibly small [14,15]. Vanishing of the RCS contribution at the exact quasi-RCS point requires that we take into account the full k 1 and Q 2 1,2 dependence of the hadronic tensor.…”
Section: Calculation Of B N In the Forward Kinematicsmentioning
confidence: 99%
“…In Refs. [8,9,10,11] (double) logarithms of the type log(Q 2 /m 2 l ) were advocated in connection with the transverse beam SSA in elastic lepton-nucleon scattering. Such logarithmic terms might also increase the beam SSA in DIS considered here.…”
Section: Two-photon Exchange In Inclusive Dismentioning
confidence: 99%